Profesi Akuntan Ditinjau Dari Segi Hukum - Sundarta, M. Imam (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
Purpose: Growth accountant profession is still low when compared with the graduation degree in Accounting a larger each of year, this means that the basic problems that arising to the transfer of accounting undergraduate do not wish to become a professional accountant. This study reviewing the legal aspects of the accountant profession the accountant constraining growth in Indonesia, and the difficulty to become a professional accountant for many of the rules that are a barrier to growth accounting profession when compared with other professions as convenience may be able to achieve the profession as an Advocate and Notary, etc Design/metholodology/approach: For that reason legal research can not beregarded as following the methodology of social sciences in general. This study uses a qualitative study of law, and social interpellation and constructivism assume that the fact that the dimension plural, interactive and inter-professional legal experience exchange. Finding: a legal vacuum since 1954 until 1999, as Law No. 34 in 1954 about accounting, and finance minister's decision number 331 / KMK.017 / 1999 on the Implementation of Accountant registration in the State Register in the constitution Originiality/value: Accounting profession itself is not hardly ever discuss legal views. Right now try to study the law in terms of the Constitution. Accounting for this title used by the accounting profession, so that the law could resolve this whole thing